BUDAYA POLITIK NEGARA MAJU DAN NEGARA BERKEMBANG: SUATU PERBANDINGAN - Suryo, Herning (Transformasi, 2015)
The political culture of a society reflect a pattern of behavior in the life of the state, butbecause of the political culture also may reflect a common value system of a society which hasthe awareness to participate in collective decision making and determination of public policy forthe whole community.From the comparison of the political culture in the developed and developing countries(United States, China and Indonesia), it has a distinctive political culture and identity as afeature of the country. Each country seeks to transform towards democratic politics by using apolitical culture that is rooted in the community, so that these countries achieve what is aspiredto national interests.In the context of this comparison, Indonesia can be said to approach the development ofa democratic political culture of the United States and China. Indonesia has implementeddemocratic elections and has implemented presidential election through the national convention.Thus, Indonesia certainly has a relatively advanced political culture and want to learn at everystages toward democracy.Keyword: comparison; democracy; state